Local Wisdom Found in Mangongkal Holi Tradition - M. Silalahi, Charles David; Sibarani, Robert; Setia, Eddy (KnE Social Sciences, 2019)
Mangongkal Holi is known as the highest level of tradition on Batak Toba daily life practices. Previously, this tradition was done by those limited families for the reasons of funding and its complicated management. But nowadays, the practice of mangongkal holi tradition is more rarely to be found; eventhough there are many local wisdom implicitly impressed on it. This study is part of the first writer’s dissertation, entitled Tradisi Mangongkal Holi pada Masyarakat Batak Toba (Mangongkal Holi Tradition in Batak Toba Society). This research was done in qualitative research, the data were collected through direct participatory observation, in-depth interviews with many batak toba informants (adat’s experts, practitioners and academicians/theologians), as well as audio-visual documentation. The data were analyzed by using Miles, and Huberman model; where data condensation, data display and data conclusion/verification were the three concurrent flows activities done to make sure the process of data analysis precisely on the track. The final conclusion of this research state that there were nine local wisdom found in mangongkal holi tradition, they are: thanksgiving, respect, humble/humility, blessings, responsibility, mutual cooperation, prays, concession in dialogue, and prestige; where all these local wisdom will be well-stored and longlasting while mangongkal holi tradition conserved through good and acceptable design of recommended revitalization model. The writers believe that there are still many solutions to solve the problems of funding, such as: down-grading the level of ceremony, or unifying more individual saring-sarings in a mangongkal holi ceremony. Keywords: Mangongkal Holi, Local Wisdom, Oral Tradition, Batak Toba.